Challenges in Post Merger Integration an analysis based on a case study from CEE - Vodák, Martin (2011)
The thesis is covering an analysis of a concrete acquisition case from CEE. Based on the review of theory a conceptual framework was created and then applied to the acquisition case in order to analyze the process of post-merger integration. As a result, recommendations were created for similar future transactions.